Monimuotoinen ansiotyö - Haapakorpi, Arja; Järvensivu, Anu; Kauhanen, Merja; Melin, Harri (Tampere University Press, 2022)
This edited volume discusses multiple job holding as part of Finnish working life. The articles in this book examine this little researched phenomenon through a wide range of empirical data. Based on Statistics Finland's register data, different ways of combining jobs are classified. Interview material sheds light on the conditions for holding multible jobs. A new perspective is provided by the chaos theory of careers.